Metabolic effects of interleukin-6 in human splanchnic and adipose tissue - Lyngsø, Dorthe (Blackwell Science Inc, 2002)
Interleukin-6 (IL-6) was infused intravenously for 2.5 h in seven healthy human volunteers at a dose giving rise to a circulating IL-6 concentration of ≈35 ng l(−1). The metabolic effects of this infusion were studied in subcutaneous adipose tissue on the anterior abdominal wall and in the splanchnic tissues by the Fick principle after catheterizations of an artery, a subcutaneous vein draining adipose tissue, and a hepatic vein, and measurements of regional adipose tissue and splanchnic blood flows. In control studies without IL-6 infusion subcutaneous adipose tissue metabolism was studied by the same technique in eight healthy subjects. The net release of glycerol and fatty acids from the subcutaneous abdominal adipose tissue remained constant in the control experiment. IL-6 infusion gave rise to increase in net glycerol release in subcutaneous adipose tissue while the net release of fatty acids did not change significantly. In the splanchnic region IL-6 elicited a pronounced vasodilatation, and the uptake of fatty acids and the gluconeogenic precursors glycerol and lactate increased significantly. The splanchnic net output of glucose and triacylglycerol did not change during the IL-6 infusion. It is concluded that IL-6 elicits lipolytic effects in human adipose tissue in vivo, and that IL-6 also has effects on the splanchnic lipid and carbohydrate metabolism.